Micro vapor bubble jet flow for safe and high-rate fluorescence-activated cell sorting. Issue 7 (2nd March 2017) - de Wijs, Koen; Liu, Chengxun; Dusa, Alexandra; Vercruysse, Dries; Majeed, Bivragh; Tezcan, Deniz Sabuncuoglu; Blaszkiewicz, Kamil; Loo, Josine; Lagae, Liesbet
Abstract : High rate and safe cell sorting is enabled by rapid thermal bubble jet flow in a closed microfluidic chip. Abstract : Safe, high-rate and cost-effective cell sorting is important for clinical cell isolation. However, commercial fluorescence-activated cell sorters (FACS) are expensive and prone to aerosol-induced sample contamination. Here we report a microfluidic cell sorter allowing high rate and fully enclosed cell sorting. The sorter chip consists of an array of micro heating hotspots. Pulsed resistive heating in the hotspots produces numerous micro vapor bubbles with short duration, which gives rise to a rapid jet flow for cell sorting. With this method, we demonstrated high sorting rate comparable to commercial FACS and the significant enrichment of rare cancer cells. This vapor bubble based cell sorting method can be a powerful tool for contamination-free and affordable clinical cell sorting such as circulating tumor cell isolation and cancer cell therapy.